2006
DOI: 10.1111/j.1442-9071.2006.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of open‐ and closed‐globe trauma presenting to Cairns Base Hospital, Queensland

Abstract: The incidence of ocular trauma in far north Queensland is equal to other Australian populations. However, there is a disproportionately high incidence in the Aboriginal and Torres Strait Islander population. Alcohol-related assault is a significant cause of visual loss in the Aboriginal and Torres Strait Islander population. Closed-globe injuries are more common than open globe; however, the latter have poorer visual prognosis. Initial visual acuity of all injuries correlated with final visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
79
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 26 publications
11
79
4
1
Order By: Relevance
“…9 Incidence rates of open-globe injuries in regional Australia have been reported to be similar, with incidence rates of 4.7 and 3.7 per 100,000 person-years for northern New South Wales and far North Queensland, respectively. 6,10 Our open-globe eye injury incidence estimates are lower than previous reports.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…9 Incidence rates of open-globe injuries in regional Australia have been reported to be similar, with incidence rates of 4.7 and 3.7 per 100,000 person-years for northern New South Wales and far North Queensland, respectively. 6,10 Our open-globe eye injury incidence estimates are lower than previous reports.…”
Section: Discussioncontrasting
confidence: 54%
“…3 There have been several previous epidemiological reports on eye trauma in Australia. [3][4][5][6][7][8][9][10][11] Young males have been noted to be at particular risk of injury. Work-related eye trauma has been identified as a significant public health concern, with protective eyewear compliance at suboptimal levels.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in the literature reported that an age of <5 years or an increased age, eyelid injury, injuries with retrolimbal involvement, wound length of >5 mm, globe rupture, vitreous hemorrhage, retinal detachment, and relative afferent pupillary defect were risk factors for a final best-corrected visual acuity. [7,8,17,[29][30][31][32][33][34] In our study, the risk factor analysis revealed that there was no significant parameter that affected final visual acuity in children, although age was the only protective factor. In adults, age, additional surgical procedure, and initial visual acuity were significant as risk factors.…”
Section: Discussionmentioning
confidence: 84%
“…[4,5] Compared with closed eye injuries, open injuries have poorer prognosis. [6][7][8] OGIs, which represent a substantial proportion of ocular traumas, accounts for a substantial proportion of ocular trauma-related hospital expenditure (>60%) and supposes a significant financial burden. [9] The estimation of final visual acuity just after OGI is important for both patients and physicians who deal with its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…2 There are few prospectively collected data in the literature but other contemporary prospective studies quote similar patterns in the incidence of ocular trauma, for example 4.9 per 100 000 in Southern Italy 6 and 11.8 per 100 000 in Australia. 7 Previously, the age distribution for the occurrence of serious ocular trauma was found to be bi-modal, with the maximum incidence in young adults and a second peak in the elderly. 8,9 However, this appears to be evolving with a single large peak observed for young adults, especially males.…”
Section: Eyementioning
confidence: 99%